Auditory gamma oscillations predict global symptomatic outcome in the early stages of psychosis: A longitudinal investigation. Issue 11 (November 2018) - Koshiyama, Daisuke; Kirihara, Kenji; Tada, Mariko; Nagai, Tatsuya; Fujioka, Mao; Ichikawa, Eriko; Ohta, Kazusa; Tani, Motoko; Tsuchiya, Maiko; Kanehara, Akiko; Morita, Kentaro; Sawada, Kingo; et al.
Highlights: 40-Hz auditory steady-state response (ASSR) predicts the prognosis in early psychosis in this study. 40-Hz ASSR reduction correlates with global symptomatic outcome after 1–2 years. 40-Hz ASSR may be a useful biomarker of the long-term prognosis in early psychosis. Abstract: Objectives: The gamma-band auditory steady-state response (ASSR) is thought to reflect the function of parvalbumin-positive γ-aminobutyric acid (GABA)-ergic interneurons and may be a candidate biomarker in early psychosis. Although previous cross-sectional studies have shown that gamma-band ASSR is reduced in early psychosis, whether reduced gamma-band ASSR could be a predictor of the long-term prognosis remains unknown. Methods: In this longitudinal study, we investigated the association between gamma-band ASSR reduction and future global symptomatic or functional outcome in early psychosis. We measured 40-Hz ASSR in 34 patients with recent-onset schizophrenia (ROSZ), 28 ultra-high risk (UHR) individuals, and 30 healthy controls (HCs) at baseline. After 1–2 years, we evaluated the global assessment of functioning (GAF) in the ROSZ (N = 20) and UHR (N = 20) groups. Results: The 40-Hz ASSR was significantly reduced in the ROSZ and UHR groups. The attenuated 40-Hz ASSR was correlated with the future global symptomatic outcome in the ROSZ, but not in the UHR groups. Conclusions: A reduction in the gamma-band ASSR after the onset of psychosis may predict symptomatic outcomes in early psychosis. Significance: Gamma-band ASSR may be a potentially useful biomarker of the long-term prognosis in patients with recent-onset schizophrenia.